Densidade populacional de pratylenchus spp. em pastagens de brachiaria spp. e sua influência na disponibilidade e na qualidade da forragem - de Carvalho, Cassia; Fernandes, Celso Dornelas; dos Santos, Jaime Maia [UNESP]; Macedo, Manuel Claudio Motta (FapUNIFESP (SciELO), 2013)
The aim of this work was to evaluate the population density of Pratylenchus brachyurus and Pratylenchus zeae associated with Brachiaria brizantha, B. decumbens and B. humidicola and their influence on forage availability and quality. The experiment was conducte in the Hisaeda Farm, Terenos, MS, Brazil. Soil, roots and plant aerial part were harvest with ten replications each, in one square meter randomized sets encompassing three treatments: Good, Intermediary and Bad, visually characterized, considering the percentage of green material. P. brachyurus and P. zeae density were evaluated in soil and plant roots. Dry matter of green, dead and re-growth materials, plant nutritional status and forage quality were assessed in the aerial plant part. Soil fertility was determined in all harvested samples. Both nematode species were identified from all samples, with a larger numbe in the roots (between 87-311 P. brachyurus and 1-61 P. zeae.10 g-1) than in the soil (0-8 P. brachyurus and 1-39 P. zeae.200 cm-3), however, no significant differences were found in the number of specimens between treatments. Considering that these forage species are perennial and host Pratylenchus spp, there is a tendency to increase the population of these pathogens over time, becoming a serious phytosanitary problem.
Population density of Pratylenchus spp. In pastures of Brachiaria spp. And its influence on the forage availability and quality
Keywords: B. decumbens; B. humidicola; Brachiaria brizantha; P. zeae; Poaceae; Pratylenchus brachyurus